Un período que no hable de política al presente, es lo mismo que un fusil sin cañon : imprensa periódica e a construção da identidade oriental (Província Cisplatina - 1821-1828) - Winter, Murillo Dias (2014)
The historical period beginning with the dissolution of colonial ties and the subsequent revolutions of independence in the american continent was of transformation of the power structures and the emergence of new forms of state administration and local identification. Process taken, generally, from the concept of nation. In those years the fluidity of identity and political relations, several groups vied for the leadership of the process, divided between cities and domains before determined by the colonial occupation of Spain and Portugal. In the Banda Oriental, the intersection point between the Spanish and Portuguese old domains in America, the turning point was the consummation of the Luso-Brazilian domination in the region by the creation of the Cisplatin Province (1821-1828). Period that embraces the Cisplatin Congress (1821) to the Preliminary Convention of Peace (1828). One of the key elements of the dispute was the periodical press, at boiling point and vertiginous growth - made possible by the new Lusitanian conjuncture - during this period of political uncertainties, in Brazil, as much as in the United Provinces of the River Plate, such as the Cisplatin. In this context of great questioning and instability, characterized by the variety and fluidity of relationships, political projects, and also the transformation of some key concepts, the periodical press was constituted as the main instrument of discussion and exchange of ideas, becoming an essential tool to make and discuss local and international politics. Another characteristic of the periodicals at that time was, in the process of building a local identity, Oriental, differentiate those from the brazilian invaders and portenho neighbors. The different newspapers appropriated and discussed fundamental concepts such as homeland, nation and public opinion, , way to defend their political projects. Focusing on the uses of some of these key concepts, recurring in the debates, the paper analyzes the peculiarities of a speech that has created a strong enough image to provide distinctive elements for the creation, in 1828, of the Eastern Republic of Uruguay